Well-being in schools: a conceptual model - Konu, Anne; Rimpelä, Matti (Health Promotion International, 2002)
Health and well-being have mostly been separated from other aspects of school life. Health services and health education have been available for school-aged children in Western societies for a long time. Recently, more comprehensive school health programmes have been developed, e.g. the WHO ‘health promoting school’ and ‘coordinated school health programme’ in the USA. They focus on how to implement health promotion and health education in school. However, a theoretically grounded model based on the sociological concept of well-being is needed for planning and evaluation of school development programmes. The School Well-being Model is based on Allardt's sociological theory of welfare and assesses well-being as an entity in school setting. Well-being is connected with teaching and education, and with learning and achievements. Indicators of well-being are divided into four categories: school conditions (having), social relationships (loving), means for self-fulfilment (being) and health status. ‘Means for self-fulfilment’ encompasses possibilities for each pupil to study according to his/her own resources and capabilities. ‘Health status’ is seen through pupils' symptoms, diseases and illnesses. Each well-being category contains several aspects of pupils' life in school. The model takes into account the important impact of pupils' homes and the surrounding community. Compared with others, The School Well-being Model's main differences are the use of the well-being concept, the definition of health and the subcategory means for self-fulfilment. Making the outline of the well-being concept facilitates the development of theoretically grounded subjective and objective well-being indicators.